The role of acceleration, maximum velocity, and speed endurance in sprint performance - Mohammed Nadim Abd; Jihad Mohammed Hassan Al Eqabi; Haider Radhi Raheem Alsaedi; Bareq Rahman Hashim Alfadhli; Mustafa Mohsin Flayyih Khlaifawi (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Sprint performance is governed by the interplay of acceleration, maximum velocity, and speed endurance. Although these components have been studied independently, their combined influence on 100m and 400m performance remains underexplored. A comprehensive understanding of their interdependence is critical for refining evidence-based training strategies.